School Choice, Student Performance, and Teacher and School Characteristics : The Chilean Case - Vegas, Emiliana (The World Bank, 1999)
Vegas explores how schools change in response to increased competition generated by voucher programs in Chile. A unique data set provides information on teacher demographics and labor market characteristics, as well as teachers' perceptions of school management. When teacher data are marched with school-level data on student achievement using a national assessment data set (SIMCE), some teacher and school characteristics affect student performance, but a great deal of unexplained variance among sectors remains important in predicting student outcomes. Teacher education, decentralization of decisionmaking authority, whether the school schedule is strictly enforced, and the extent to which teachers have autonomy in designing teaching plans and implementing projects all appear to affect student outcomes. Interestingly, teacher autonomy has positive effects on student outcomes only when decisionmaking authority is decentralized. This paper--a product of Public Services, Development Research Group--is part of a larger effort in the group to understand the role of incentives in education. The author may be contacted at evegas@worldbank.org